Performance of soybean pre-emergence herbicides to control the spectrum of weeds (Research, Society and Development, 2023)
With the objective of evaluating the effectiveness and agronomic practicality of herbicides applied at different doses, in pre-emergence, in the control of weeds and selectivity for soybean crops, a study was carried out at the experimental farm of the University of Rio Verde - GO (UniRV). When sowing soybeans, the NS 7709 IPRO cultivar was used. After sowing, herbicide treatments were applied in a plant-apply system. Eddus EC applied in pre-emergence promotes higher percentages of control of Digitaria insularis, Digitaria horizontalis, Eleusine indica and Cenchrus echinatus at the lowest approved dose of 1.5 L p.c. ha-1, being superior to Spider and similar to the herbicides Zethamaxx, Dual Gold and Boundary. The higher approved dose of Eddus EC (2.5 L p.c. ha-1) promotes higher percentages of control of Commelina benghalensis and Ipomoea grandifolia, being similar and superior to the parent herbicides (Spider, Zethamaxx and Boundary). Lesser doses of Eddus EC will also promote excellent levels of control in the validated data. No symptoms of poisoning were observed in the soybean plants NS 7709 IPRO in the validated data, 28 days after application, in the application of two herbicide treatments. The highest soybean yields were obtained in the plots that received the application of Eddus EC in a dose of 2.5 L p.c. ha-1 and Zethamaxx, with 4946.8 and 4868.3 kg ha-1, respectively. The Eddus EC herbicide is presented as an excellent option for the management of damaged plants in the pre-emergence of soybeans NS 7709 IPRO.